"ASSESSMENT OF NUTRITIONAL STATUS OF CHILDREN AGE 1 to 24 MONTHS" - M; Froozani; B Bahreini (Tehran University of Medical Sciences, 1977)
For detection of mild to moderate degrees of malnutrition, mid- arm-head circumference ratio of 458 of low income children of Isfahan were studied. The percentage bf children with a mid-arm-head circumference ratio of above 0.310, between 0.310 and 0.280, between 0.279 and 0.250, and less than 0.250 were 31.00, 51.75, 15.28 and 1.97 respectively. A significant correlation was found between the weight of children and their ratio of arm circumference to head circumference.